2019
DOI: 10.1177/1040638719852144
|View full text |Cite
|
Sign up to set email alerts
|

Zinc overload in weaned pigs: tissue accumulation, pathology, and growth impacts

Abstract: Zinc oxide (ZnO) is commonly fed to pigs at pharmacologic concentrations (2,000–3,000 ppm) for the first 3 wk post-weaning to increase growth and reduce enteric bacterial disease. The safety of this high-dose treatment is assumed based upon lower bioavailability of ZnO compared to other common forms of Zn in feed; however, limited data are available regarding the specific serum and tissue concentrations of Zn expected in animals experiencing overload following feeding of excessive ZnO. Fifty-five 3-wk-old pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
2
19
1
Order By: Relevance
“…17 Similarly, there was no significant difference in body weight between treated and control pigs. 1,4 However, the exposure periods were shorter and the ZnO concentrations were lower than in our study.…”
contrasting
confidence: 73%
See 2 more Smart Citations
“…17 Similarly, there was no significant difference in body weight between treated and control pigs. 1,4 However, the exposure periods were shorter and the ZnO concentrations were lower than in our study.…”
contrasting
confidence: 73%
“…4 It has been reported that high doses of ZnO (4,000–6,000 ppm, 3 wk) induce pancreatic acinar cell apoptosis. 1 Nevertheless, we found no reports of Zn poisoning in farm-reared pigs; histologic and immunohistochemical examinations of their organs and tissues are lacking.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The large and prolonged employment of ZnO at pharmacological levels in pig farming has raised several concerns, as depicted in Figure 2. Too high or too much protracted ZnO supplementations lead to the loss of ZnO benefits with the potential onset of toxic effects [22,61,62], because of the excessive accumulation of Zn in animal tissues such as kidney, liver, and pancreas [63,64], which can experience Zn overload [62].…”
Section: Risks Related To Pharmacological Levels Of Znomentioning
confidence: 99%
“…In addition, the form of the trace mineral (e.g., inorganic vs. organically-complexed) can influence these interactions and its bioavailability [ 2 ]. Moreover, feeding supra-nutritional or pharmacological levels of a trace mineral could lead to mineral imbalances and deficiencies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%